Temporal changes in glochidia larval occurrence and condition index in freshwater mussels, Lamellidens marginalis (Lamarck, 1819) collected from a wetland of Bangladesh - Salam, Md. Abdus; Biswas, Shishir; Hossain, Md. Sazzad; Sultana, Nur-A; Uddin, Md. Jasim (Journal of Fisheries, 2024)
Information on glochidia larval occurrence and release time from the brooding mussels are crucial for the development of larval rearing system or commercial collection of juveniles from the wilds. We report monthly changes in glochidia larval occurrence and condition index (CI) in freshwater mussel, Lamellidens marginalis, collected from a wetland in Bangladesh. Specimens were drawn monthly over a year from October 2021 to September 2022. Lamellidens marginalis females displayed glochidia larvae in the supra-branchial chamber over ten months from March to December. No glochidia larva was reported in females during January and February when the water temperature remained below 18°C. All females carried glochidia larvae during March and April, indicating no larval shedding at this time. The percentage of females containing glochidia larvae dropped suddenly in May (22.22%), suggesting that glochidial release from the gill chamber to the environment was initiated by May. Larval presence in only some females (22% to 86%) at each sampling date from May to September implied an extended glochidial discharge period till September when the water temperature was above 24°C. The CIs varied from 0.36 to 0.79, with two distinct peaks in December and March when all females carried glochidia larvae. In conclusion, monthly changes in larval occurrence and discharge could be primarily related to temperature and the existence of larvae in mussels could affect the CIs in L. marginalis.